ChemInform Abstract: Asymmetric Synthesis of Spiroketals with Aminothiourea Catalysts. Issue 17 (April 2016) - Yoneda, Naoki; Fukata, Yukihiro; Asano, Keisuke; Matsubara, Seijiro
Abstract: The intramolecular bis‐cyclization of α, β‐unsaturated carbonyl compounds (I) tethered with an hydroxy substituted alkylketone side chain is optimized in the presence of bifunctional thiourea catalyst to give spiroketals.